MEMBACA AL- QURAN SEBAGAI MEDIA UNTUK MENENANGKAN PIKIRAN, MENGURANGI STRES DAN RELAKSASI - Ipin Tajul Aripin; Dede Aji Mardani (Program Studi Hukum Keluarga Islam, 2024)
Since it was revealed more than 14 centuries ago, the Quran is considered the holy words of Islam, and is believed to provide psycho-spiritual therapeutic benefits to its readers and/or listeners. In this context, listening to the Quranic verses rhythmically, among Muslims is often seen as a form of murotal. However, compared to music, rhythm, book-novel reading and meditation therapies, information regarding the neural basis of the healing effects based on the Quran remains largely unexplored. In this narrative review, the researcher presents and discusses work related to neural, mental correlates that highlights some methodological issues and proposes recommendations to advance this emerging transdisciplinary research. Collectively, evidence suggests that listening to rhythmic-murotal Quranic verses activates similar brain regions and produces similar theraptic effects compared to music and rhythm therapy. Nonetheless, further research is needed with a more concise research design involving standardized neorology, brain, neuroscience and health experts to strengthen these findings, and pave the way for listening to Quranic verses as an effective psycho-spiritual therapy.